2012
DOI: 10.1371/journal.pone.0051187
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Management: Under What Conditions Do Sámi Pastoralists Manage Pastures Sustainably?

Abstract: Community-based management (CBM) has been implemented in socio-ecological systems (SES) worldwide. CBM has also been the prevailing policy in Sámi pastoral SES in Norway, but the outcomes tend to vary extensively among resource groups (“siidas”). We asked why do some siidas self-organize to manage common pool resources sustainably and others do not? To answer this question we used a mixed methods approach. First, in the statistical analyses we analyzed the relationship between sustainability indicators and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 41 publications
0
42
1
Order By: Relevance
“…The recently emerged livestock production cooperatives belong to community-based resource management (CBRM), and more in-depth analyses about the performance of the new institutional arrangement are still needed. The studies about CBRM in other pastoral systems showed that CBRM can work and fail in sustainable governance of pastures under different conditions (Hausner et al 2012). In addition, market economy has created new opportunities for herders to diversify their livelihood sources.…”
Section: Resultsmentioning
confidence: 99%
“…The recently emerged livestock production cooperatives belong to community-based resource management (CBRM), and more in-depth analyses about the performance of the new institutional arrangement are still needed. The studies about CBRM in other pastoral systems showed that CBRM can work and fail in sustainable governance of pastures under different conditions (Hausner et al 2012). In addition, market economy has created new opportunities for herders to diversify their livelihood sources.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, several socioecological studies have been published, following the line of thought of Ostrom (). In these studies, the focus is on nomadic herders incentives, the likelihood of cooperation among production units and conflicts between traditional pasture management systems and state administrative systems and policy (Hausner, Fauchald, & Jernsletten, ; Næss & Bårdsen, , ; Næss, Bårdsen, & Tveraa, ; Turi & Keskitalo, ; Tveraa, Stien, Brøseth, & Yoccoz, ; Ulvevadet & Hausner, ).…”
mentioning
confidence: 99%
“…Saami herders have reported that communication and reciprocal cooperation are strong on the summer pastures in Finnmark, but that trust is lacking on winter pastures (Hausner et al 2012). While this study focussed on cooperation within and between summer siidas, future work should investigate cooperative and competitive behaviours in winter siidas, where land tenure changes may create barriers to mobility and resource-access, and so potentially prove detrimental to a cooperative reindeer husbandry.…”
Section: Discussionmentioning
confidence: 99%